The Affordances of MacKinnon Ravine: Fighting Freeways and Pursuing Government Reform in Edmonton, Alberta - Bower, Shannon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
This article examines the disputes that erupted in the second half of the twentieth century over the proposal to build a freeway through Edmonton’s MacKinnon Ravine, a landscape some saw as fundamental to the city’s network of recreational lands along the North Saskatchewan River and its extensive ravine system. MacKinnon Ravine, as a possibility-rich landscape, helped successive waves of urban activists articulate opposition to freeway development by serving as the keystone in a multi-decadal arc of civic activism. An orientation to the ravine allowed a series of distinct advocacy efforts to build on each other both in methods and in goals. These successive waves of activism not only altered MacKinnon Ravine’s future but also helped reshape civic governance in Edmonton.